2016
DOI: 10.1007/s11192-015-1792-2
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary topics of information science: a study based on the terms interdisciplinarity index series

Abstract: Interdisciplinarity is increasingly widespread. Many technological frontiers and hotspots are emerging in the intersecting research areas. The existing measurement indexes of interdisciplinarity are mostly based on the co-occurrence of authors, institutions, or references, and most focus on the tendency to interdisciplinarity. This paper introduces a new measurement index entitled topic terms interdisciplinarity (TI) for interdisciplinarity topic mining. Taking Information Science & Library Science (LIS) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…The first method involves an index series named terms interdisciplinarity (TI index), which attempts to recognize topics by calculating TI values together with Bet values and term frequency values and analyzes the evolution of interdisciplinary sciences based on social network analysis and time-series analysis. A study has proved that the TI value can identify IDR topic terms well (Xu et al,2016). The second method is an integrated method for IDR topic recognition and prediction, which integrates various methods, including co-occurrence networks analysis, high-TI terms analysis, and burst detection, and offers an overall perspective into interdisciplinary topic identification (Dong et al, 2018).…”
Section: Comparative Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first method involves an index series named terms interdisciplinarity (TI index), which attempts to recognize topics by calculating TI values together with Bet values and term frequency values and analyzes the evolution of interdisciplinary sciences based on social network analysis and time-series analysis. A study has proved that the TI value can identify IDR topic terms well (Xu et al,2016). The second method is an integrated method for IDR topic recognition and prediction, which integrates various methods, including co-occurrence networks analysis, high-TI terms analysis, and burst detection, and offers an overall perspective into interdisciplinary topic identification (Dong et al, 2018).…”
Section: Comparative Analysis and Discussionmentioning
confidence: 99%
“…Leydesdorff et al (2013) visually displayed both the citing and cited interdisciplinary citation matrices using Rao-Stirling indicators. Xu et al (2016) introduced a measurement index called topic terms interdisciplinarity (TI) for IDR topic mining. They showed that the TI value can identify IDR topic terms effectively.…”
Section: Idr Measurement Indexmentioning
confidence: 99%
“…Unlike other indexes, it overcomes at least partially the issue of an arbitrary choice of a predefined categorization (Cassi et al, 2014). Therefore, Stirling's diversity index is more systematic or robust for measuring interdisciplinarity than other indexes (Stirling, 2007;Leydesdorff and Rafols, 2011), such as Shannon's index (Rafols and Meyer, 2010;Karlovcec and Mladenic, 2015), or TF-IDF (Xu et al, 2016). Second, researchers have used social network analysis to calculate measurements of interdisciplinarity, such as network coherence or a similar network of publications (Rafols and Meyer, 2010), degree centrality of a co-occurrence network among disciplines, and betweenness centrality of the citation network among journals (Leydesdorff, 2007;Leydesdorff and Rafols, 2011).…”
Section: Bibliometric Studies On Interdisciplinaritymentioning
confidence: 99%
“…Based on published papers , researchers investigated interdisciplinarity in the following research areas : chemistry [ 9 ], physics [ 10 ], nanoscience and nanotechnology[ 11 13 ], biotechnology [ 14 ], information science and library science [ 15 18 ], humanities [ 19 ], bionanoscience [ 3 , 20 ], Japanese rice research and technology development [ 21 ], biochemistry and molecular biology [ 22 ], medical science [ 23 ], and biotechnology [ 24 ]. The problem regarding studies based on published papers is the incomplete collection of bibliographic data, although this issue has recently been addressed from a technical perspective [ 25 ].…”
Section: Introductionmentioning
confidence: 99%